2023
DOI: 10.26668/businessreview/2023.v8i7.3045
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Compensation, Job Rotation, Employee Engagement and Employees Performance of SMEs

Abstract: Purpose: The purpose of this study is to analyze the relationship between compensation and employee performance, analyze the relationship between job rotation and employee performance, and analyze employee engagement on employee performance in SMEs.   Design/Methodology/Approach: The method used in this study is quantitative to test the hypothesis taken from the research variables in numbers and then the data is analyzed using statistical procedures. This study explains the causal relationship between variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Lastly, the study found that employee involvement has a positive and significant impact on all four aspects of employee productivity, including employee commitment, competency, congruence, and job satisfaction. This result corroborates the findings of previous studies, such as Sunarsi et al (2020), Khan et al (2023), andAmbarwati et al (2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lastly, the study found that employee involvement has a positive and significant impact on all four aspects of employee productivity, including employee commitment, competency, congruence, and job satisfaction. This result corroborates the findings of previous studies, such as Sunarsi et al (2020), Khan et al (2023), andAmbarwati et al (2023).…”
Section: Discussionsupporting
confidence: 93%
“…By involving employees in organizational decision-making and day-to-day activities, various favorable outcomes can be achieved. Research studies such as Ambarwati et al (2023) have analyzed the relationship between employee involvement and employee performance in 670 SMEs, and the results indicate a significant correlation between the two factors. Similarly, the studies conducted by Sunarsi et al (2020) and Khan et al (2023) have concluded that organizations can achieve high employee loyalty and increased job performance through employee involvement.…”
Section: Employee Involvementmentioning
confidence: 99%
“…On this basis, it benefits the organization indirectly because employees have more skills that give management more opportunities to plan work and adapt to expected changes. and filling possible vacancies (Ambarwati et al, 2023). Therefore, job rotation is called cross-training, which means that an employee of a unit or department can learn various job skills during a specific period of time.…”
Section: Theoretical Background 21 Concept and Definition Of Job Rota...mentioning
confidence: 99%
“…The aim of this study is to examine the impact of transformational leadership on job performance, specifically focusing on the mediating roles of self-efficacy and creativity among salespersons in Vietnamese small and medium-sized enterprises (SMEs) (Murphy & Anderson, 2020;Ricardianto et al, 2020). The unique context of Vietnamese SMEs provides an interesting setting to explore the relationship between transformational leadership and job performance, considering the cultural and organizational characteristics prevalent in this context (Ambarwati et al, 2023;Curado & Santos, 2022).…”
Section: Introductionmentioning
confidence: 99%